Granular Carbon-Based Electrodes as Cathodes in Methane-Producing Bioelectrochemical Systems - Liu, Dandan; Roca-Puigros, Marta; Geppert, Florian; Caizán-Juanarena, Leire; Na Ayudthaya, Susakul P.; Buisman, Cees; ter Heijne, Annemiek (Frontiers in Bioengineering and Biotechnology, 2018)
Methane-producing bioelectrochemical systems generate methane by using microorganisms to reduce carbon dioxide at the cathode with external electricity supply. This technology provides an innovative approach for renewable electricity conversion and storage. Two key factors that need further attention are production of methane at high rate, and stable performance under intermittent electricity supply. To study these key factors, we have used two electrode materials: granular activated carbon (GAC) and graphite granules (GG). Under galvanostatic control, the biocathodes achieved methane production rates of around 65 L CH4/m2catproj/d at 35 A/m2catproj, which is 3.8 times higher than reported so far. We also operated all biocathodes with intermittent current supply (time-ON/time-OFF: 4’- 2’, 3’- 3’, 2’- 4’). Current-to-methane efficiencies of all biocathodes were stable arund 60% at 10 A/m2catproj and slightly decreased with increasing OFF time at 35 A/m2catproj, but original performance of all biocathodes was recovered soon after intermittent operation. Interestingly, the GAC biocathodes had a lower overpotential than the GG biocathodes, with methane generation occurring at -0.52 V vs. Ag/AgCl for GAC and at -0.92 V for GG at a current density of 10 A/m2catproj. 16S rRNA gene analysis showed that Methanobacterium was the dominant methanogen and that the GAC biocathodes experienced a higher abundance of proteobacteria than the GG biocathodes. Both cathode materials show promise for the practical application of methane-producing BESs.